CQI: improving teaching and learning through assessment and evaluation / Norul Fadhilah Ismail and Farizuwana Akma Zulkifle - Ismail, Norul Fadhilah; Zulkifle, Farizuwana Akma (Universiti Teknologi MARA, Negeri Sembilan, 2024)
Continuous Quality Improvement (CQI) is a process that uses assessments together information about the effectiveness of educational program design, delivery, and direction. This feedback is then used to make improvements, which in turn lads to further assessment and evaluation, creating a continuous cycle of improvement. In education, CQI aims to enhance teaching and learning by identifying problem areas for improvement, analysing root cause, implementing solutions, and monitoring evaluating outcomes.